Corrosion behaviour of bismuth‐containing gold thick‐film electrodes. Issue 12 (26th May 2017) - Junker, N.; Schneider, M.; Michaelis, A.
Abstract : The electrochemical behaviour of a bismuth‐containing gold thick‐film, which was screen‐printed and co‐fired on low temperature co‐fired ceramic (LTCC), has been investigated in 1 M nitric acid. After potentiostatic polarisation the material was electrochemically studied by voltammetry to determine the degradation kinetics and the role of elements of the glass‐ceramic compounds. Field emission scattering electron microscopy (FESEM) examinations and energy dispersive X‐ray (EDX) analyses confirm the electrochemically driven degradation of the composite: The interphase between the thick‐film and the LTCC substrate was selectively attacked around the conductive gold layer. Elementary bismuth was reductively formed within the attacked area. Inverse voltammetric analyses of the electrolyte solution show that the electrochemical degradation is superimposed by chemical degradation of bismuth‐containing glass‐phases. The reductively formed bismuth was removed from the screen‐printed electrode (SPE) due to the subsequently performed anodic polarisation. The amount of anodically dissolved bismuth is comparable with the coulometrically determined value of the anodic polarisation sweep. Abstract : A Bi(III)‐containing gold‐thick‐film, screen‐printed and co‐fired on LTCC, was used as electrode material. Due to cathodic polarisation of this screen‐printed electrode metallic bismuth was reductively formed in the interphase between the thick‐film and the LTCC substrate. In a subsequent anodic treatment the previously formed bismuth was anodically dissolved, leaving behind a degraded interphase.